BRANDING BASED ON DIGITAL MARKETING FOR SURABAYA STUDENTS: HIGH PURCHASE DECISION? - Devangga Putra Adhitya Pratama; Muhlisin (International Journal of Economics, Science, and Education, 2024)
The trend of the last few years shows a significant amount and uses it mostly for social media, especially for students. The gap between the limited purchasing power due to the lack of individual income makes students not have enough purchasing power to make transactions. On the other hand, students easily have a desire because of digital marketing on their social media. Based on this background, this research was conducted to analyze the effect of digital marketing-based branding on purchasing decisions in the marketplace. This is done to get an idea of how much the impact of product branding using digital marketing can change a person's purchasing decision. The method that researchers use is the descriptive causality quantitative method with data collection using an online form. To determine the sample, the author uses probability sampling with a Purposive Sampling approach. The respondents were 90 people who met the previously established answer criteria. The analysis techniques used are data quality test, the classical assumption test, and multiple linear regression. Based on this research, it shows that product branding and social media variables partially do not have a positive and significant effect on purchasing decisions. The magnitude of the influence of product branding and social media tiktok on purchasing decisions is 11.2%. Then the remaining 88.8% is influenced by other variables not examined in this study.